Espiritualidade manifesta: sitcom Friends em diálogo com princípios de Leonardo Boff sobre espiritualidade - Almeida, Paulo Felipe Teixeira (2014)
This research seeks to discuss an uncommon reflection about spirituality. The background for this reflection mostly takes place within the cosmopolitan urban context. The main goal of this research is to provide a dialogue between a representation of reality, from the urban context, through the analysis of a spirituality manifested in the sitcom Friends, and through the eyes of Leonardo Boff and his perspective on spirituality. Thus, if it is possible to sketch a vision of this, imagine someone in front of the TV, watching episodes of Friends with the indicated texts Boff in his hands. Better yet, imagine someone sitting next to Boff, both watching the hit series and sharing their perceptions in a friendly dialogue, both devoted to recognizing points of correlation between what the theologian thinks, says, and writes, and what composes the series in audio, image, and movement. This specific approach to Boff s work, Virtues: For Another Possible World, aims to create these unusual dynamics. There is dialogue, however, with several authors from different traditions, in addition to research on media/television culture and spirituality. This research sheds the assumption that you can find possibilities to understand television in its everyday representation. Similarly, it approaches the allusion that contemporary theological thinking seeks answers over a spirituality experienced in an urban and cosmopolitan environment. To represent this cosmopolitan environment, the research elects the sitcom Friends as a timely manifestation and representation of this reality that is ever so relevant to our way of life. At the other end, but with the expectation of a point of correlation, the research lists perspectives of the work and the thoughts of Leonardo in regards to spirituality. To do so, the research starts with general definitions of spirituality, and then a definition relevant for this research. It continues by providing a definition of what a sitcom is beyond the sitcom Friends. From this point on, proposals about spirituality are agreed on, namely implicit spirituality (traces/remnants of faith that survives not dependent on or committed to a tradition), explicit spirituality (religious formalities and legacies tied to ambiguous traditions of faith), and spirituality manifested (friendship/fellowship in elements such as hospitality, conviviality, and commensality present themselves to start and maintain themselves). In this last characterization of spirituality (manifested), the research seeks to understand and analyze, in the sitcom Friends, issues such as hospitality, conviviality, and commensality; and, following, a highlight of when these issues lead to another level of communion: marriage. Finally, a the research engages in a discussion and proposed (re)reading of the conduit, positioning and relationship of our faith communities in urban and cosmopolitan contexts.